Factors affecting the successful implementation of MS1500 by Malaysian halal food industry - Permata Sari, Dian; Jaswir, Irwandi; Haji Che Daud, Mohd Radzi (2021)
Since no specific Halal Act has been established and applied by Malaysian Government yet, up to this day Malaysian Standard, MS1500 is the only basic reference to issue a Halal Certificate for Halal Food which should applied by the legal authority such as JAKIM (Jabatan Kemajuan Islam Malaysia) and State Islamic religious council. Therefore, Malaysian Government is eager to see the successful implementation this MS as their leading Halal Standard. However, there are many problems and challenges that frequently lead to unsuccessful execution of implementation of this MS. Accordingly, this study aims to identify the factors affecting the successful implementation of MS1500 thoroughly. A series of analysis had been performed: started with data preparation and screening followed by Exploratory Factor Analysis (EFA) and reliability test. The next steps of analysis are Confirmatory Factor Analysis (CFA) and Validity Test. This study identified that Perception On Implementation (POI), Halal Control System Activity (HCSA) and Owner, Management, Employee Limitation (OMEL) are the factors affecting the successful of Implementation of MS1500. On top of that, it was also found that in Malaysia, finance and regulation were not the factors that cause the limitation on implementation of Halal Food Standards